2010
DOI: 10.1002/chem.200903390
|View full text |Cite
|
Sign up to set email alerts
|

Cavity‐Shaped Ligands: Calix[4]arene‐Based Monophosphanes for Fast Suzuki–Miyaura Cross‐Coupling

Abstract: Five conical calix[4]arenes that have a PPh(2) group as the sole functional group anchored at their upper rim were assessed in palladium-catalysed cross-coupling reactions of phenylboronic acid with aryl halides (dioxane, 100 degrees C, NaH). With arylbromides, remarkably high activities were obtained with the catalytic systems remaining stable for several days. The performance of the ligands is comparable to a Buchwald-type triarylphosphane, namely, (2'-methyl[1,1'-biphenyl]-2-yl)diphenylphosphane, which in c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
34
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 66 publications
(36 citation statements)
references
References 43 publications
(88 reference statements)
1
34
0
Order By: Relevance
“…Recently, Matt and Se´meril showed that cavity-shaped ligands could bring an added value in the efficiency of the Suzuki-Miyaura coupling. 12 Furthermore, although cavity-shaped tetraphosphines derived from calixarenes, 13 resorcinarenes 14 or cyclodextrins 15 (CDs) have been synthesized, none of them has been probed in a low-loading catalytic system to the best of our knowledge. In addition, we have shown that perbenzylated CDs regioselectively functionalized with two phosphines could serve as pseudo-enantiomeric platforms in enantioselective catalysis.…”
mentioning
confidence: 99%
“…Recently, Matt and Se´meril showed that cavity-shaped ligands could bring an added value in the efficiency of the Suzuki-Miyaura coupling. 12 Furthermore, although cavity-shaped tetraphosphines derived from calixarenes, 13 resorcinarenes 14 or cyclodextrins 15 (CDs) have been synthesized, none of them has been probed in a low-loading catalytic system to the best of our knowledge. In addition, we have shown that perbenzylated CDs regioselectively functionalized with two phosphines could serve as pseudo-enantiomeric platforms in enantioselective catalysis.…”
mentioning
confidence: 99%
“…88 Thus, bromocalixarene 18 was alkylated in the presence of sodium hydride to afford 19-22 which, upon halogen-lithium exchange, followed by reaction with Ph 2 PCl yielded 13-16. Debenzylation of 14 using AlCl 3 gave 17.…”
Section: Methodsmentioning
confidence: 99%
“…Notably also, these catalysts remained stable for several days. 88 In order to study phosphorylation which occurs in biochemical processes, the phosphatase inhibitory properties of compounds 28 and 29 have been investigated. 89 In these experiments it was found that the introduction of methylenebisphosphonic acid 28 onto calix [4]arene 30 to form compounds such as 33 and 34, results in the efficient inhibition of alkaline phosphatase whereas this inhibition of 28 itself is only very low.…”
Section: Methodsmentioning
confidence: 99%
“…Secondly, the calixarenes could provide exceptionally useful platforms for preparing multidentate ligands with convergent binding sites. The results reported in the literature with calixarene-based ligands indicated that organic solvent and elevated reaction temperature were still necessary to ensure complete conversion for palladium-catalyzed SuzukieMiyaura cross-coupling reaction [38,39]. Thirdly, calixarenes have been attracting much attention, due to their remarkable ability to recognize and discriminate metal ions as specific receptors.…”
Section: Introductionmentioning
confidence: 97%